Pengembangan Branding Digital dan Platform Online untuk Meningkatkan Daya Saing UMKM di Dusun Kiringan, Bantul - Irfan Hanif Indranegara (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
MSMEs play an important role in economic growth, but still face challenges in branding and digital marketing. Kiringan Hamlet, as one of the traditional herbal medicine production centers, is experiencing obstacles in marketing their products due to the lack of attractive visual identity and minimal utilization of digital technology. This service program aims to assist MSMEs in Kiringan Hamlet in improving their branding and competitiveness through logo and packaging redesign and website design as a digital marketing medium. The methods used include observation, interviews, solution design, and digital-based design implementation. The results of this program show that the new logo design and packaging stickers increase product attractiveness and strengthen MSME brand identity. In addition, the website design provided a digital solution to expand market reach. The evaluation showed that MSME players responded positively to this contribution and began to realize the importance of digital branding in marketing. With this program, it is expected that MSMEs in Kiringan Hamlet can be more developed and able to compete in a wider market with more effective digital branding and marketing strategies.